Exam Ref AZ-800 : configuring Windows Server hybrid advanced services - Thomas, Orin, 1973- (Microsoft Press, 2023)
Prepare for Microsoft Exam AZ-801 and demonstrate your real-world mastery of configuring and managing Windows Server on-premises, hybrid, and Infrastructure as a Service (IaaS) platform workloads. Designed for professionals with Windows Server and Azure experience, this Exam Ref focuses on the critical thinking and decision-making acumen needed for success at the Microsoft Certified: Windows Server Hybrid Administrator Associate level.